2015
DOI: 10.1016/s1002-0160(15)30053-9
|View full text |Cite
|
Sign up to set email alerts
|

Biochar and Compost Increase Crop Yields but the Effect is Short Term on Sandplain Soils of Western Australia

Abstract: (Received , 201; revised , 201) ABSTRACT Sandplain soils on the south coast of Western Australia have low inherent fertility, which is mainly due to poor nutrient retention caused by insufficient clay and organic colloidal material. Previous research has shown the benefits in nutrient levels and retention from adding clay to sandplain soils; however, there is almost no information on the addition of organic amendments. A field experiment was established at the Esperance Downs Research Station, \\Testern Aus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…For instance, biochar produced at different temperatures varied in their effect on N uptake by Eruca sativa (Zhou et al, 2017) and on growth of lettuce (Hunter et al, 2017). High temperature during pyrolysis increased stability of biochar in soil (Mašek et al, 2013), but had short-lived effects on crop yields (Hall and Bell, 2015;Griffin et al, 2017). Moreover, Hagner et al (2016) reported that pyrolysis temperature only marginally influenced biochar-induced effects on soil pH, water holding capacity (WHC), soil organisms, and plant growth.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, biochar produced at different temperatures varied in their effect on N uptake by Eruca sativa (Zhou et al, 2017) and on growth of lettuce (Hunter et al, 2017). High temperature during pyrolysis increased stability of biochar in soil (Mašek et al, 2013), but had short-lived effects on crop yields (Hall and Bell, 2015;Griffin et al, 2017). Moreover, Hagner et al (2016) reported that pyrolysis temperature only marginally influenced biochar-induced effects on soil pH, water holding capacity (WHC), soil organisms, and plant growth.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Fecondo et al [ 27 ] found that the use of 40 Mg ha −1 of compost significantly increased durum wheat yields in comparison with mineral fertilization in rotation with tomato. Other studies confirm the positive effect of compost on bread wheat yields in Australia [ 29 ] and in Italy by comparing the effects of organic commercial fertilizers and compost on durum wheat yields in an organic agriculture context [ 30 , 33 ]. In the light of existing literature, the preliminary results presented in this study seem to open the way to the replacement of ordinary N-fertilizers with no detrimental effects on durum wheat yield, at least in the Mediterranean rainfed cereal–forage cropping systems.…”
Section: Discussionmentioning
confidence: 82%
“…While several studies on the influence of biowaste compost [ 27 ], composted sewage sludge [ 28 ] and biochar [ 29 , 30 ] on durum wheat have been carried out, to our knowledge no similar studies have been published about the fertilization effect of BFAs on durum wheat.…”
Section: Introductionmentioning
confidence: 99%
“…Coastal sand has sufficient groundwater resources, and is not affected by floods and can be utilized throughout the year for crop cultivation [11]. However, coastal sand land has the main constraints of low nutrient availability both macro and micro nutrients [12,13] as well as low nutrient storage ability [14]. In order to support the success of soybean cultivation in coastal sand, besides using adaptive soybean cultivar (genotype), it also requires production input in the form of organic matter.…”
Section: The Utilization Of Samas Beach Sand Land In Bantul Regency Smentioning
confidence: 99%